2015
DOI: 10.1017/s1092852915000371
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging endophenotypes in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that has a strong genetic basis, and is heterogeneous in its etiopathogenesis and clinical presentation. Neuroimaging studies, in concert with neuropathological and clinical research, have been instrumental in delineating trajectories of development in children with ASD. Structural neuroimaging has revealed ASD to be a disorder with general and regional brain enlargement, especially in the frontotemporal cortices, while functional neuroimaging stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 266 publications
(347 reference statements)
1
26
0
Order By: Relevance
“…Several studies have focused on both anatomical and functional brain imaging, revealing volumetric abnormalities using different techniques such as structural MRI (sMRI), structural connectivity through diffusion-weighted imaging studies, diseaserelated functional activation patterns and functional connectivity via functional MRI (fMRI) and resting-state fMRI (rs-fMRI). Consistent data have been obtained regarding the increased growth of total gray matter and the white matter volume (Courchesne et al, 2001;Sparks et al, 2002;Hardan et al, 2006;Hazlett et al, 2011;Mahajan et al, 2015;Ismail et al, 2016).…”
Section: Introductionsupporting
confidence: 71%
“…Several studies have focused on both anatomical and functional brain imaging, revealing volumetric abnormalities using different techniques such as structural MRI (sMRI), structural connectivity through diffusion-weighted imaging studies, diseaserelated functional activation patterns and functional connectivity via functional MRI (fMRI) and resting-state fMRI (rs-fMRI). Consistent data have been obtained regarding the increased growth of total gray matter and the white matter volume (Courchesne et al, 2001;Sparks et al, 2002;Hardan et al, 2006;Hazlett et al, 2011;Mahajan et al, 2015;Ismail et al, 2016).…”
Section: Introductionsupporting
confidence: 71%
“…These findings contribute to the notion that the trajectory of brain maturation in ASD is atypical and involves an early period of overgrowth, with each brain region having its distinct trajectory [35,36]. Further structural neuroimaging studies have revealed ASD to be a disorder with general and regional alterations in brain size, while functional neuroimaging studies have highlighted changes in connectivity between brain regions in ASD patients [35,[37][38][39]. The review by Li et al summarizes recent progress from neuroimaging studies in young ASD children and discusses the applicability of these results in aiding ASD diagnosis [40].…”
mentioning
confidence: 58%
“…Autism spectrum disorders (ASD) are a collection of developmental neurobehavioral conditions that include autistic disorder, Asperger's disorder, and pervasive developmental disorder (Dow, 2012). ASD is predominately a heritable disorder with estimates as high as 80-90% (Mahajan and Mostofsky, 2015). Epidemiologic studies suggest that some cases of autism can be attributed to environmental factors such as toxic exposures, teratogens, perinatal insults, and prenatal infections such as rubella and cytomegalovirus (Muhle et al, 2004).…”
Section: Multiple Sclerosis and Autismmentioning
confidence: 99%